2015
DOI: 10.1016/j.jnucmat.2015.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic rate equation modeling of trapping/detrapping of hydrogen isotopes in tungsten materials

Abstract: International audienceCode development to solve numerically the model equations of diffusion and trapping of hydrogen in metals. Parametrization of the model trapping parameters (detrapping energies and density): fitting of experimental TDS spectrum. Confrontation model/experiment: evolution of retention with fluence and implantation temperature. Investigation of period of rest between implantation and TDS on retention and depth profile. a b s t r a c t Relevant parameters for trapping of Hydrogen Isotopes (HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
96
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(102 citation statements)
references
References 28 publications
5
96
0
1
Order By: Relevance
“…A modification of our experimental setup is planned in order to address precisely this point. We believe that our experimental results demonstrate the importance of deuterium trapping on natural defects of tungsten and we expect that this would help to rationalize the physical mechanism behind the law at 300 K [19,31,32] and would allow safer extrapolation of the tritium wall inventory for ITER.…”
Section: Discussionmentioning
confidence: 71%
“…A modification of our experimental setup is planned in order to address precisely this point. We believe that our experimental results demonstrate the importance of deuterium trapping on natural defects of tungsten and we expect that this would help to rationalize the physical mechanism behind the law at 300 K [19,31,32] and would allow safer extrapolation of the tritium wall inventory for ITER.…”
Section: Discussionmentioning
confidence: 71%
“…One-dimensional (1D) MRE codes are frequently used for extracting energetic information about the interaction of PFC materials with ion beams and plasmas [2,5,13]. We have recently developed such a code, MHIMS (for migration of hydrogen isotopes in materials) [4], which describes numerous elementary steps encountered in real experiments. With MHIMS, one can simulate the implantation of hydrogen isotopes below the surface with their subsequent diffusion into the bulk or toward the surface and their trapping on bulk defects.…”
Section: Mre Models: Single Trap-single Detrapping Energymentioning
confidence: 99%
“…Secondly, we give an overview of the experimentally explored parameter space. Then we present the MRE codes MHIMS [4] and MHIMS-Reservoir [9] which are used to construct tungsten wall models that will be tested on the experimental results. In section 3, we first elaborate on the parametrization of the MHIMS code, mostly on experimental inputs, and we estimate how far the model is able to reproduce experimental observations and draw conclusions on its achievements and failures.…”
Section: Introductionmentioning
confidence: 99%
“…Hodille et al [188] reported that H atoms should be retained in three different types of traps, with binding energies of 0.83, 1.0 and 1.5 eV between 300 and 700 K. This is in good agreement with the results presented in this Chapter, as the simulations reveal that the main trapping of H atoms is in monovacancies, from H 5 V 1 to H 1 V 1 . The values of the traps proposed by Hodille et al [188] can be assimilated to those used in the simulations presented in this Chapter, as can be seen in the comparison shown in …”
supporting
confidence: 86%
“…The values of the traps proposed by Hodille et al [188] can be assimilated to those used in the simulations presented in this Chapter, as can be seen in the comparison shown in …”
mentioning
confidence: 99%